Aplikasi Six Sigma dan Design of Experiment untuk Peningkatan Mutu Proses Kain Cotton Tetoron (Studi Kasus Perusahaan Tekstil) - Ni Made Sudri; Yenny Widianty; Anissa Fernanda (Institut Teknologi Indonesia, 2020)
Improvement of Textile Industry system design with Six Sigma and FMEA to improve process quality. Six Sigma is a method of continuous quality improvement, by minimizing the number of defects. FMEA (Failure Mode Effect Analysis) tool is used to help determine the appropriate action, eliminating priority failure modes. The next step to improve to determine the most influential factor to the occurrence of color defects, so that the influence of the interference factor is minimum. If the control function is carried out and the factors causing the defect do not appear again there will be an increase in sigma value. FMEA analysis results obtained by machine temperature and material factors that most influence the occurrence of color defects, with RPN values of 210 and 120 respectively, the Six Sigma calculation results an increase in sigma value from initial conditions of 3.78 sigma to 4.93 sigma, or an increase in process capability of 1.15 sigma. Proposed improvements with DOE so that color defects do not appear are suggested by setting the thermosol engine temperature control device and mixing the optimized NaCl. Keyword : Six Sigma, FMEA, DOE